IMPLEMENTASI MODEL GAME BASED LEARNING DALAM PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Tri Kuntari, Fadila; Anggraeni Siwi, Dwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science and Social Studies (IPAS) learning is often considered challenging and uninteresting for elementary school students. The Game Based Learning (GBL) model has emerged as an innovative solution to increase student motivation and understanding. This study aims to describe the implementation of the GBL model and the obstacles encountered in IPAS learning among fifth-grade students at SD Negeri Jombor 03 Sukoharjo. Using a descriptive qualitative approach, this study collected data through observation, in-depth interviews with teachers and students, and documentation studies. Data validity was strengthened by triangulation techniques. The results show that the implementation of GBL went through the stages of planning, implementation, and evaluation by utilizing various educational games. The application of this model succeeded in creating a fun and interactive learning atmosphere, as evidenced by increased enthusiasm, active questioning, and ease of understanding the material by students. However, there were major obstacles in the form of limited facilities and infrastructure as well as suboptimal time management. These findings confirm that GBL is effective in increasing learning motivation, but requires careful planning to overcome technical challenges in the field.